1998
DOI: 10.23986/afsci.5614
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and phosphorus losses in surface runoff and drainage water after application of slurry and mineral fertilizer to perennial grass ley

Abstract: Losses of nitrogen (N) and phosphorus (P) from perennial grass ley on a fine sand soil were studied with five treatments: no fertilizer (1), cow slurry applied in autumn (2), winter (3) or spring (4), and mineral fertilizer applied in spring (5). For N, the total amounts applied (1992-96) were 0, 772, 807, 805 and 510 kg ha-1 and for P 0, 141, 119, 143 and 107 kg ha-1, respectively. In the first year (establishment of the ley, 1992-93), N losses (drainage + surface runoff) were slightly higher after applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 14 publications
4
35
0
2
Order By: Relevance
“…The cumulative load of NO 3 -N in surface runoff was small in all treatments (0.8-2.2 kg ha -1 ), being highest in the IN plots over the 3-year study phase. The small NO 3 -N losses in surface runoff from grass are consistent with results from studies of Uhlen (1978), Turtola and Kemppainen (1998), Ridley et al (2001), Smith et al (2001), and Saarijärvi (2008). Ploughing of grass soil in October 2000 increased slightly losses of NO 3 -N and TN in surface runoff but decreased NH 4 -N losses (Table 4).…”
Section: Nitrogen Losses In Surface Runoffsupporting
confidence: 88%
See 2 more Smart Citations
“…The cumulative load of NO 3 -N in surface runoff was small in all treatments (0.8-2.2 kg ha -1 ), being highest in the IN plots over the 3-year study phase. The small NO 3 -N losses in surface runoff from grass are consistent with results from studies of Uhlen (1978), Turtola and Kemppainen (1998), Ridley et al (2001), Smith et al (2001), and Saarijärvi (2008). Ploughing of grass soil in October 2000 increased slightly losses of NO 3 -N and TN in surface runoff but decreased NH 4 -N losses (Table 4).…”
Section: Nitrogen Losses In Surface Runoffsupporting
confidence: 88%
“…Injection further reduced the originally small surface runoff losses of NH 4 -N and TN by 83% (p < 0.001) and 34% (p < 0.01), respectively, compared with surface broadcasting, although a little more slurry TN (20-30 kg ha -1 yr -1 ) was spread on the IN plots. On a fine sandy soil, Turtola and Kemppainen (1998) measured great annual N losses in surface runoff from grass with autumn broadcast slurry, 16-36 kg ha -1 yr -1 and 7.7-22 kg ha -1 yr -1 for TN and NH 4 -N, respectively. In their study, however, the amount of TN applied in autumn was one-third higher and the volumes of surface runoff were three times greater than in Phase II of our study.…”
Section: Nitrogen Losses In Surface Runoffmentioning
confidence: 97%
See 1 more Smart Citation
“…uble P concentration of this layer increases and may lead to higher loss of P by surface runoff and drainage water (Turtola and Jaakkola 1995, Turtola and Kemppainen 1998, Turtola and YliHalla 1999). This risk is very possible, because currants are often cultivated on coarse mineral soils and slope fields.…”
Section: Niskanen R Nutritional Status In Currant Fieldsmentioning
confidence: 99%
“…For example Niinioja (1993) reported that in several empirical studies in Nordic countries, N leaching from fields fertilized by manure varied between 1 and 58 kg N ha -1 yr -1 . Turtola and Kemppainen (1998) reported that annual N losses in surface runoff and drainage water varied between 5-40 kg N ha -1 from grass fields fertilized by slurry. Jaakkola (1984) reported N leaching of 1-38 kg N ha -1 yr -1 from clay soil fields under grass or cereal production and Vuorenmaa et al (2002) 13.8-16.2 kg N ha -1 yr -1 as specific loss from the arable land part of agricultural research catchments.…”
Section: Discussionmentioning
confidence: 99%